Quitting smoking before surgical interventions and its relationship to health literacy - Özgünay, Seyda Efsun; Demirci, Hakan; Eminoğlu, Şermin; Dülger, Seyhan; Yılmaz, Canan; Karasu, Derya; Şengören Dikiş, Özlem (The European Research Journal, 2019)
Objectives: The aim of our study was to evaluate the effect of health literacy (HL) level and smoking dependence of patients on their compliance with advice given by the physicians in anesthesia polyclinics on giving up smoking. Methods: This prospective study included 165 smokers. HL was evaluated by The European Health Literacy (HLS-EU). Nicotine dependence was measured by Fagerstrom test for nicotine dependence (FTND). Patients were advised not to smoke and their carbon monoxide levels in expired air were measured before on the operation day. Results: The number of patients smoking on the day of surgery was significantly higher among females (p = 0.001). While the HL was lower, the FTND scores (p = 0.006), daily cigarette consumption (p < 0.001) and years of cigarette smoking (p = 0.002) were found to be significantly higher. Fewer number of days between the polyclinic interview and the surgery date were positively correlated with compliance with the advice to give up smoking (p = 0.011). Conclusions: Since the number of patients continuing to smoke cigarettes was high, it was concluded that verbal advice on giving up smoking is not enough and that other more effective measures are needed to ensure patient compliance. The reminder of 'quit smoking' on the day very close to the surgery may help more patients to stop smoking on that day.